Prognostic Value of Plasma and Urine Glycosaminoglycan Scores in Clear Cell Renal Cell Carcinoma - Gatto, Francesco; Maruzzo, Marco; Magro, Cristina; Basso, Umberto; Nielsen, Jens (Frontiers in Oncology, 2016)
The prognosis of metastatic clear cell renal cell carcinoma (ccRCC) vastly improved since the introduction of antiangiogenic targeted therapy. However, it is still unclear which biological processes underlie ccRCC aggressiveness and affect prognosis. Here, we checked whether a recently discovered systems biomarker based on plasmatic or urinary measurements of glycosaminoglycans aggregated into diagnostic scores correlated with ccRCC prognosis. Thirty-one patients with a diagnosis of ccRCC (23 metastatic) were prospectively enrolled and their urine and plasma biomarker scores were correlated to progression-free survival (PFS) and overall survival (OS) as either a dichotomous (“Low” vs. “High”) or a continuous variable in a multivariate survival analysis. The survival difference between “High” vs. “Low”-scored patients was significant in the case of urine scores (2-year PFS rate = 53.3% vs. 100%, p = 310-4 and 2-year OS rate = 73.3% vs. 100%, p = 0.0078) and in the case of OS for plasma scores (2-year PFS rate = 60% vs. 84%, p = 0.0591 and 2-year OS rate = 66.7% vs. 90%, p = 0.0206). In multivariate analysis, the urine biomarker score was an independent predictor of PFS (HR: 4.62, 95% CI: 1.66 to 12.83, p = 0.003) and OS (HR: 10.13, 95% CI: 1.80 to 57.04, p = 0.009). This is the first report on an association between plasma or urine GAG scores and the prognosis of ccRCC patients. Prospective trials validating the prognostic and predictive role of this novel systems biomarker are warranted.